2014
DOI: 10.1128/aac.00104-14
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Antiviral Activity of Low-Dose Ritonavir in Boosted Protease Inhibitor Regimens

Abstract: Protease inhibitors are largely used for the treatment of HIV infection in combination with other antiretroviral drugs. Their improved pharmacokinetic profiles can be achieved through the concomitant administration of low doses of ritonavir (RTV), a protease inhibitor currently used as a booster, increasing the exposure of companion drugs. Since ritonavir-boosted regimens are associated with long-term adverse events, cobicistat, a CYP3A4 inhibitor without antiviral activity, has been developed. Recently, high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
(34 reference statements)
1
9
1
1
Order By: Relevance
“…This is a first important conclusion of our study that raises concerns on the need of full dose of ritonavir-boosted ATV in Caucasian patients and opens new questions about the ATV dosages that should considered correct (or in label and off label in Europe). This may be particularly relevant in light of the recent findings showing that ritonavir may accumulate at intracellular level at higher degree than other PIs providing additional antiviral activity and eventually allowing the use of reduced PI doses [ 33 ]. We also found that such patients have the highest risk of experiencing ATV-related complications and may benefit from TDM-driven adjustments in ATV dosage with potential advantages in terms of costs and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This is a first important conclusion of our study that raises concerns on the need of full dose of ritonavir-boosted ATV in Caucasian patients and opens new questions about the ATV dosages that should considered correct (or in label and off label in Europe). This may be particularly relevant in light of the recent findings showing that ritonavir may accumulate at intracellular level at higher degree than other PIs providing additional antiviral activity and eventually allowing the use of reduced PI doses [ 33 ]. We also found that such patients have the highest risk of experiencing ATV-related complications and may benefit from TDM-driven adjustments in ATV dosage with potential advantages in terms of costs and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs associated concentrations of antituberculars, expressed in ng/mL, were obtained using the following formula: antitubercular amount (ng) / number of PBMCs × MCV (fL) × 10 −12 . [11][12][13][14][15]…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Importantly, while Rtv has activity against HIV, possibly leading to the development of drug-resistance mutations to PIs in cases of suboptimal regimens, Cobi is devoid of intrinsic activity against HIV replication. 19 , 20 Recently, Drv 800 mg and Cobi 150 mg have become available in an FDC (Rezolsta; Johnson and Johnson, New Brunswick, NJ, USA).…”
Section: Drv-cobi-ftc-taf Pharmacokineticsmentioning
confidence: 99%